'Bias in, Bias out': gender equality and the future of work debate. (3rd April 2019) - Howcroft, Debra; Rubery, Jill
ABSTRACT: The future of work debate is cast with the certainty that technology-driven change is inevitable as numerous pundits profiteer from predicting the future. Among the many books, conferences, workshops and consultancy reports, there is a notable silence regarding the impact on gender. The aim of this article is to present a corrective, by arguing that if the gender bias that is embedded in the current social order is not tackled head-on, the future world of work is likely to exacerbate gender equality gaps.